2012
DOI: 10.1055/s-0032-1322591
|View full text |Cite
|
Sign up to set email alerts
|

Successful Endovascular Treatment of Carotid Aneurysms in a Patient with Vascular Ehlers-Danlos Syndrome

Abstract: This case report suggests that endovascular treatment of ICA aneurysms is feasible and can be achieved in patients with vascular EDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Vascular EDS patients have a high risk of mortality due to vascular fragility that often leads to hemorrhage (De Paepe and Malfait 2012). Intracranial aneurysms have been reported in both classical and non-classical forms of EDS, but relatively speaking it is patients with the vascular subtype of EDS who are at the highest risk for IBA formation (Chen et al 2013;Kato et al 2001;Kim et al 2016;Lummus et al 2014;Mirza et al 1979;Oderich et al 2005;Schievink et al 1990Schievink et al , 2002. Kim et al (2016) found intracranial aneurysms in 12 individuals, seven of whom had vascular EDS, from a chart review of 99 EDS patients (mean age 41.7 years) who underwent brain imaging.…”
Section: Ehlers-danlos Syndromementioning
confidence: 99%
“…Vascular EDS patients have a high risk of mortality due to vascular fragility that often leads to hemorrhage (De Paepe and Malfait 2012). Intracranial aneurysms have been reported in both classical and non-classical forms of EDS, but relatively speaking it is patients with the vascular subtype of EDS who are at the highest risk for IBA formation (Chen et al 2013;Kato et al 2001;Kim et al 2016;Lummus et al 2014;Mirza et al 1979;Oderich et al 2005;Schievink et al 1990Schievink et al , 2002. Kim et al (2016) found intracranial aneurysms in 12 individuals, seven of whom had vascular EDS, from a chart review of 99 EDS patients (mean age 41.7 years) who underwent brain imaging.…”
Section: Ehlers-danlos Syndromementioning
confidence: 99%
“…Many of these aneurysms are pseudoaneurysms that arise as a result of trauma,2 9 21 iatrogenic injury,10 15 16 22 23 infection,7 19 radiation,8 11 22 25 or genetic abnormalities, such as fibromuscular dysplasia14 and Ehlers–Danlos syndrome 24. In our case, chronic otitis media is a possible etiology with progressive erosion into the left ICA, although we cannot rule out iatrogenic injury given a history of tympanoplasty.…”
Section: Discussionmentioning
confidence: 77%
“…In this review, there were 36 cases 6,7,10,16,27,28,30,36,38,39,41,48,51,[53][54][55][56]59,60,63,66,[70][71][72][73][74]78,[80][81][82]85,88 treated with interventional or surgical parent vessel occlusion only without bypass (Table 3).…”
Section: Treatment Strategies and Results From Literature Reviewmentioning
confidence: 99%